Sie sind auf Seite 1von 4

Sequences, Series, Sigma Notation and Binomial Theorem

Types of Sequences

1. Arithmetic Progression: a, a + d, a + 2d, … , a + (n-1)d, …

2. Geometric Progression: a, ar, ar 2 , … , ar n-1 , …

3. Others: u 1 , u 2 , u 3 , … , u n , … in general.

Notation
Notation
Meaning
a
First term of a sequence, particularly in an AP or GP.
d
Common difference of an AP.
r
Common ratio of a GP.
T n or u n
nth term of sequence.
S n
Sum of the first n terms of a series. This notation is used particularly in the
context of AP and GP before the introduction of the sigma notation. The
series in context need not necessarily be an AP or GP.
Formulae
Description
AP
GP
nth term
n
−1
T
=
a
+ (
n
−1)
d
T
=
ar
n
n
Sum of the first n
terms
n
n
a
(1 −
r
S n =
(2
a
+
(
n
1)
d
)
S
=
) is applicable for all
2
n
1 − r
values of r ≠ 1
n
S
=
(
a
+
T
)
where
n
n
2
T
=
a
+ (
n
−1)
d
is the last
n
term or nth term.
Sum to infinity
-
a
=
which exists provided
S n
1 −
r
−1 <
r < 1
Common
d
=
T
T
r
=
T
÷
T
n
n −1
n
n −1
difference/ratio
Mean
Arithmetic mean of x and y is
x + y .
Geometric mean of x and y is
±
xy .
2
Sequences in general (AP, GP or otherwise).
Description
Using the notation S n and T n
Using the sigma notation
Sum of the first n
terms
S
= T + T + T +…+ T
n
n
1
2
3
n
u
= u + u + u +
+ u
r
1
2
3
n
r
= 1

http://education.helixated.com An Open Source Education Project

1

nth term
T
=
S
S
n
n
− 1
n
n
n −1
u
=
u
u
n
r
r
r =
1
r
=
1
First term
T
= S
1
1
1
u =
u
1
r
r
= 1
Sum from the
(m+1)th term to
the nth term
S
− S = T + T
+ + T
n
m
n
m
m
+
1
m
+
2
n
u
u
= u
+ u
+
+ u
r
r
m
+
1
m
+
2
n
r =
1
r
=
1

Example 1: A geometric series has first term 1 and common ratio 2. Find the least value of n for which the sum of the first n terms exceeds the value 1000.

Example 2: The sum of the first 50 terms of an arithmetic series is twice that of the sum of the terms from the 26 th to the 50 th inclusive. Find the common difference of this series in terms of a where a is the first term. Find the minimum number of terms required for the sum to exceed 1300a.

Some Other Properties of Sigma Notation

1.

2.

3.

n

r =

1

(

a

r

+

b

r

)

=

n

=

1

r

a

r

+

n

=

1

r

b

r

.

n n

r =

n

1

r =

1

ka

r

a b

r

r

=

k

a

r

r =

1

n

=

≠ ⎜

r

1

a

r

where k is a constant.

⎛ ⎜

n

=

1

r

b

r

in general.

Some Standard Results

n

r = 1

r

1

1.

r

=

2

3

=

4

n

(

2

(

1)

(You are expected to know this result because it is an AP)

+

1)(2

n

+

1)

2

n +

1)

2

n n +

(

n 1

r = 1

n 1

r

r = 1

2. n n

=

6

3.

Remarks: Results for (2) and (3) will be given to you in the question if it is needed.

Example 3: Express that

http://education.helixated.com An Open Source Education Project

r

2 n

= n + 1

(

r r +

1)

in terms of n given that

2

n 1

r

= 1

r

2

=

6

n n

(

+

1)(2

n

+

1)

.

Method of Differences

If

a

r

, the general term of a sigma notation

f (r +1) f (r)

, then we have

=

n

r

= 1

n

r =

1

[

f

f

(

r

+

1)

(

r

+

1)

f

(

)

n

r

]

r

=

1

f

(

r

)

n

r = 1

a

r

, can be expressed in the form

=[f (2) + f (3) + f (4) +f (n) + f (n +1)][f (1) + f (2) + f (3) + f (4) + + f (n)]

= f (n +1) f (1)

1

Example 4: Express (

r +

1)(

r +

2)

in the form

A

r +

1

+

B

r

+ 2

. Hence, or otherwise, find

n

r

= 1

1

(

r

+

1)(

r

+

2)

in terms of n and deduce the value of

r

= 1

1

(

r

+

1)(

r

+

2)

.

Binomial Theorem

There are 2 formulae with 2 different conditions and applications.

y + ⎛ ⎜ ⎜ n ⎞ ⎟ ⎟ x

n

x ⎝ ⎜ 1 ⎠ ⎟

x

1

+

+

y

)

n

x

)

n

where

=

x

n

= +

1

+ ⎜

nx

n

1

2

+

+

(

n n

1)

2

x

 2! x <1 (i.e. −1 < x < 1 )

n

2 2

y

n n

(

n

⎝ ⎟ ⎟ ⎠ x

x

1. (

2. (

+ ⎜ ⎜

2)

r

3

+

1)(

n

n

+

3!

r

y

r

+

+ +

n n

(

n

n

n

1

1)(

xy

n

1

2)

(

+

y

n

n r +

1)

r

!

r

x +

The first formula is used to expand the sum of 2 terms taken to the power of a positive

integer n. Without this formula, it is still possible to expand although it would be silly to do so.

(x + y)

n slowly, step by step,

The second formula gives us an infinite series. The term

can take values that are both positive and negative. Unlike the first formula where the power n is only restricted to positive integer, the power n in the second formula can be a

(1+ x)

n has a power n which

 fraction such as 1 or − 3 2 2

. This is definitely a much more powerful formula but the

condition for the application of the formula is much more stringent. One of the 2 terms in the bracket has to be a 1 and the range of the other term x in the bracket has to be in the

range from 1 to 1 (i.e. 1 < x < 1 ).

http://education.helixated.com An Open Source Education Project

3

Example 5: Use the binomial theorem to find the first four non-zero terms of the series

expansion of

the range of x in each case.

(4 + 3x)

1
2

in (a) ascending powers of x, (b) descending powers of x, giving

We can use the infinite geometric series

1 + +

r

r

2

+

expand

(1

+ x

)

1

easily simply by equating

r =−x .

+

r

n

+

=

1

1 r

=

(1

r

)

1

to

Example 6: Use the binomial theorem to find the first four non-zero terms of the series

expansion of (4

giving the range of x in each case.

+ x

)

1 in (a) ascending powers of x and (b) descending powers of x,

Using Partial Fraction in conjunction with Binomial Theorem

Example 7: Let

f

(

x

) =

4

2

x

+

2

x

+

6

(2

+

x

)(1

+

2

2

x

)

. Express in the form

A

Bx

+

C

+

2 + x

1

+

2x

2

and find

the series expansion of f(x) in ascending powers of x up to and including the terms in

Find the coefficient of

x 2

n

in terms of n.

4

x .

http://education.helixated.com An Open Source Education Project

4